Program Implementers' Evaluation of the Project P.A.T.H.S.: Findings Based on Different Datasets over Time - Daniel T. L. Shek; Cecilia M. S. Ma (The Scientific World Journal)
This paper integrates the evaluation findings based on program implementers in nine datasets collected from 2005 to 2009 (244 schools and 7,926 implementers). Using consolidated data with schools as the unit of analysis, results showed that program implementers generally had positive perceptions of the program, themselves, and benefits of the program, with more than four-fifths of the implementers regarding the program as beneficial to the program participants. The subjective outcome evaluation instrument was found to be internally consistent. Multiple regression analyses revealed that perceived qualities of the program and program implementers predicted perceived effectiveness of the program. In conjunction with evaluation findings based on other sources, the present study provides support for the effectiveness of the Tier 1 Program of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes) in Hong Kong.